The Influences of Trainees' Felt-Responsibility and Supervisor Support in the Transfer of Safety Training - Ana C. Freitas; Silva, S.A.; Santos,C.M. (13 th Conference of the European Academy of Occupational Health Psychology, 2018)
This study aims to analyse the relationship between the trainees’ felt responsibility and the transfer of safety training, and how this relationship is affected by the supervisors’ social support in the workplace. Training is an important component of occupational health and safety programs, developed to improve employees’ safety knowledge, attitudes and behaviors, and to protect their health. The training interventions rest on the assumption that once transferred to the workplace they will protect workers from existent and probable occupational hazards. The extent to which trainees feel personally obligated to apply the training in their work may explain their decisions and efforts to transfer. Felt-responsibility is a critical psychological state (Hackman & Oldhams, 1975, 1976, 2010), subject to environmental influences, that may help to understanding and predicting transfer-related behaviors. If trainees feel more personal responsible for transfer, they will experience greater intrinsic motivation to use the training in their work. However, empirical investigation of the felt-responsibility construct has been scarce, including in the field of the transfer of training (TT). Supervisors may reinforce and support the employees’ efforts to use training or instead they may act indifferently, give negative feedback or demonstrate an active opposition to the TT. Research has demonstrated contradictory results regarding the role of supervisor support in the TT and the studies on the role of supervisor sanctions has not been particularly extensive. Most of the empirical evidence on the TT has been conducted with employees with higher educational attainment and very little has been done from the perspective of the low qualified. This study sought to contribute to the existent knowledge on the moderator role of supervisor support and supervisor sanctions in the transfer process, in a sample of low-qualified workers. We tested a model where the relationship between the trainee’s felt responsibility and the transfer of the safety training is influenced by the moderating influence of supervisor support/sanctions. A two-time data collection was implemented among four city council blue-collar employees (n=203) who attended a fundamental safety training program. All participants were low-qualified with lower-skill jobs (i.e. jobs that require limited experience and formal education at the point of hiring - e.g, gardening, cleaning, refuse collection, etc.). Data analysis revealed that the trainees’ felt-responsibility were significantly and positively related to the TT. This effect was moderated by supervisor sanctions, but not by supervisor support. The results suggest that high sanctions aggravate the negative effect of low selfresponsibility and, unexpectedly, enhance the positive effect of high self-responsibility on TT. Our results are consistent with previous research that suggest the existence of particularities in the transfer process among low-qualified or low-skilled employees, namely on how they perceive the social support in the workplace. Our study confirms the important, although complex, role supervisors play in the safety TT and it contributes to the understanding of how social support for transfer mechanisms function among the less skilled/qualified employees. The results have implications for the design and evaluation of safety training programs, especially if aimed to these populations.